Persisting symptoms common but inability to work rare: a one-year follow-up study of Finnish hospitalised COVID-19 patients - Lindahl Anna L; Aro Miia; Reijula Jere; Puolanne Mervi; Mäkelä Mika J; Vasankari Tuula (TAYLOR & FRANCIS LTD, 2025)
Background: Difficulties in recovery persisting for months have been reported in patients with severe COVID-19. Our aim was to investigate respiratory and overall recovery one year after hospital discharge.
Methods: Finnish patients hospitalised due to COVID-19 during the first wave of the pandemic were recruited to a survey of symptoms, quality of life (RAND-36), work status, and health care use one year after hospital discharge. Patients with lung function test and chest x-ray results available from 3-6 months after hospital discharge underwent spirometry and a chest x-ray at one year.
Results: Ninety-six patients responded to the one-year survey, 32 underwent spirometry and 32 a chest x-ray. Of those working full-time before COVID-19, median duration of sick leave was 40 days and 10% had not returned to work at one year. Health-care service use related to COVID-19 after discharge was reported by 79%, 50% using primary care, 34% occupational health care and 32% specialist care, respectively. Tiredness, fatigue, and physical difficulties increased in follow-up (p = 0.022-0.033). Quality of life did not change. Chest x-ray abnormalities decreased in follow-up, with an abnormal chest x-ray in 58% at 3-6 months and 25% at one year. A restrictive spirometry pattern was more common at one year (16 vs. 34%, p = 0.014).
Conclusions: Prolonged symptoms are common, some patients have decreased lung function, and a small minority of patients still have not returned to work one year after severe COVID-19. This calls for further research into the underlying causes and risk factors for prolonged recovery.